“Factores de riesgo materno asociados a recién nacidos con retardo de crecimiento intrauterino hospital de apoyo San José – callao, 1995” - Cueva Tuanama, Milagros (1996)
The present work of research was a study applied of type cases and controls with data prospective, carried out in the Hospital of support "San José"-Callao during the year 1995; in order to identify the maternal risk factors associated to the newborn (RN) with retardation of intrauterine growth restriction (IUGR) and determine what would be the change in the study population, if the risk factor is controlled. The design was used for this purpose "Ex post facto" correlation type, which took a group of cases (A) and a group control (B). A total of 1863 births, of which 104 infants presented intrauterine growth delay, at a frequency of 5 were served. 58%, whose mothers were part of the study. After performing the respective verification of hypotheses is came to the conclusion that maternal risk factors associated with RN with IUGR are: Preconceptional: weight of the last child (0R = 9.80), age (OR = 2 99), degree of instruction (OR...)